Growth of Infants with Intestinal Failure or Feeding Intolerance Does Not Follow Standard Growth Curves - Danielle L. Morton; Keli M. Hawthorne; Carolyn E. Moore (Journal of Nutrition and Metabolism)
Objective. Infants with intestinal failure or feeding intolerance are nutritionally compromised and are at risk for extrauterine growth restriction. The aim of the study was to evaluate growth velocities of infants with intestinal failure and feeding intolerance for the first three months of age and to determine growth percentiles at birth and at 40-week postmenstrual age (PMA). Methods. A chart review of infants followed by the Texas Children’s Hospital Intestinal Rehabilitation Team was conducted from April 2012 to October 2014. Weekly weight, length, and head circumference growth velocities were calculated. Growth data were compared to Olsen growth curves to determine exact percentiles. Results. Data from infants (n=164) revealed that average growth velocities of 3-month-old infants (weight gain, 19.97 g/d; length, 0.81 cm/week; head circumference, 0.52 cm/week) fluctuated and all were below expected norms. At discharge or death, average growth velocities had further decreased (length, 0.69 cm/week; head circumference, 0.45 cm/week) except for weight, which showed a slight increase (weight, 20.56 g/d). Weight, length, and head circumference percentiles significantly decreased from birth to 40-week PMA (P<0.001). Conclusions. Growth of infants with intestinal failure or feeding intolerance did not follow standard growth curves.